SUBMARINE CAPABILITY ASSESSMENT TO INCREASE DETERRENCE EFFECT IN THE ALKI II REGION - Yoyok Nurkarya Santosa; A.B.Prasetyo; Budisantoso W; Joko Purnomo (STTAL POSTGRADUATE - INTERNATIONAL CONFERENCE, 2024)
Regional dynamics marked by an increase in submarine operations by several countries need tobe balanced with an increase in Indonesia's capabilities in underwater warfare and contribute toincreasing the country's defence system at sea. herefore, the purpose of this study is to consider thecompetitive dimension of submarine capability development on a country's deterrence effect andassess the extent of the literature review. This research is a statement that there is no instrument forassessing the capability and sustainability of submarines in an effort to increase the deterrence effectin the ALKI II region associated with the development of current dynamics so that this research isexpected to contribute to getting an instrument for assessing submarine capability and submarinedeterrence effect in the ALKI II region.